Upgrading of Intelligent Warehouse Management System Based on RFID Technology- Taking Company as an Example - Tongliang, Zhang; Xinxin, Wang; Xue, Yang (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: With the continuous development of e-commerce in China, more and more attention has been paid to modern logistics. The competition in the new era is not only in the fields of technology, cost and management, but also in the comprehensive competition of supply chain. The traditional warehouse management system is mainly completed by human resources, which consumes a lot of manpower and material resources and has low efficiency. It can no longer meet the needs of the development of modern e-commerce logistics. New retail industry is changing. New logistics has become the core of new retail form. Developing intelligent warehousing has become a solution to advance intelligent logistics. Radio Frequency Identification (RFID) technology has the advantages of large data storage, fast information reading and storage, and can effectively solve the problems of low efficiency, low accuracy and easy interference in information transmission of traditional warehouse management system. Based on the analysis of the existing problems of company A in warehouse management, this paper proposes to use RFID technology to optimize and upgrade it.